Design of Wideband SPDT RF Switch Using Switchable DGS for Sustainable Wireless Systems - Adib Othman; Noor Azwan Shairi; Huda A Majid; Faiz Asraf Saparudin; Zahriladha Zakaria; Najib Al-Fadhali (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
This paper presents a single-pole double-throw (SPDT) switch that is integrated with a thin rectangular patch switchable defected ground structure (DGS). It is a novel technology for obtaining wideband and high isolation for the SPDT switch in millimeter-wave (mm-wave) telecommunications due to the usage of switchable DGS with bandstop and bandwidth enhancement capabilities. A wideband and high isolation are required for the switchable DGS SPDT switch to operate optimally in mm-wave frequency ranges, as well as to reduce the effect of leakage signal on both the transmitter and receiver connected to the SPDT switch and hence improve system efficiency and signal integrity. The SPDT switch design was combined with two small rectangular patches switchable DGSs that could switch between bandstop and allpass responses using biasing diodes on the DGS. As a result, the suggested SPDT switch with the switchable DGS had 6 dB of insertion loss and high isolation of more than 25 dB with wideband isolation of 25.24% fractional bandwidth, which was consistent with the simulation results. Furthermore, the isolation magnitude is doubled compared to the conventional SPDT switch. This work demonstrates that integrating switchable DGS into discrete SPDT switches provides a practical solution for realizing wideband, high-isolation performance suitable for 5G mm-wave where compactness and bidirectional reconfigurability is increasingly essential for sustainable RF front-end systems.